Choosing a Partner for Social Exchange: Charitable Giving as a Signal of Trustworthiness - Sebastian Fehrler; Wojtek Przepiorka (Institute for the Study of Labor (IZA), 2016)
People benefit from being perceived as trustworthy. Examples include sellers trying to attract buyers, or candidates in elections trying to attract voters. In a laboratory experiment using exchange games, in which the trustor can choose the trustee, we study whether trustees can signal their trustworthiness by giving to charity. Our results show that donors are indeed perceived as more trustworthy and they are selected significantly more often as interaction partners. As a consequence of this sorting pattern, relative payoffs to donors and non-donors differ substantially with and without partner choice. However, we do not find donors to be significantly more trustworthy than non-donors. Our findings suggest that publicly observable generosity, such as investments in corporate social responsibility or donations to charity during a political campaign, can induce perceptions of trustworthiness and trust.
Keywords: C92; H41; 330; costly signaling; social preferences; trust; trustworthiness; partner choice; corporate social responsibility; electoral competition